KNOWLEDGE AND ATTITUDES ABOUT ANTIBIOTIC RESISTANCE AMONG THIRD-YEAR PHARMACY STUDENTS AT BINH DUONG COLLEGE OF HEALTH IN 2025 (Vietnam Journal of Community Medicine, 2026)
Phone number: 0946534411Objective: To assess the current state of knowledge and attitudes towards antibiotic resistance (AR) among third-year pharmacy students.Subjects and Methods: A cross-sectional descriptive study involving 223 students. Data were collected using a structured questionnaire to evaluate knowledge (definitions, mechanisms, contributing factors, current status, and consequences of AR) and attitudes. Descriptive statistical analysis was used; attitude scores are presented as medians and interquartile ranges (IQR).Results: 45.7% of students correctly answered the definition of AR, and 14.4% were aware of at least one mechanism of drug resistance. The majority identified contributing factors such as unnecessary broad-spectrum antibiotic use (86.1%) and over-the-counter sales (81.2%), as well as consequences like increased mortality (10.3%) and economic burden (24.7%). The overall attitude was positive (median 16; IQR: 15–18); 86.1% recognized the impact of AR on themselves/families, and 86.6% valued the role of formal education; however, 57.9% believed individuals had difficulty contributing to AR control.Conclusion: Students' knowledge about AR is still limited, especially regarding mechanisms and consequences, while attitudes are relatively positive but not linked to personal belief in contribution. There is a need to enhance training on drug resistance mechanisms, clinical-public health consequences, and the professional responsibilities of pharmacists in the rational use of antibiotics.
Keywords: Antibiotic resistance; pharmacy students; knowledge; attitudes; rational antibiotic use.